How to find the apollo landing sites - Chen, James L. (The Patrick Moore Practical Astronomy Series, 2014)
This book is for anyone who wants to be able to connect the history of lunar exploration to the Moon visible above. It addresses what Apollo equipment and experiments were left behind and what the Apollo landings sites look like now. Each Apollo mission is examined in detail, with photos that progressively zoom-in to guide the reader in locating the Apollo landing sites. Guided by official NASA photographs from the Lunar Reconnaissance Orbiter and the original Apollo missions, the reader can view the Moon with a new appreciation of the accomplishment of landing astronauts on its surface.  Countless people have gazed at the Moon in the night sky knowing the successes of the Apollo Program in landing men on the Moon. After the information in this guide, casual and serious observers can actually point out where the Apollo landings occurred as well as knowing why those sites were chosen.